2004
DOI: 10.1002/glia.20079
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β upregulates functional expression of neurokinin‐1 receptor (NK‐1R) via NF‐κB in astrocytes

Abstract: Cytokines and neuropeptides are modulators of neuroimmunoregulation in the central nervous system (CNS). The interaction of these modulators may have important implications in CNS diseases. We investigated whether interleukin-1β (IL-1β) modulates the expression of neurokinin-1 receptor (NK-1R), the primary receptor for substance P (SP), a potent neuropeptide in the CNS. IL-1β upregulated NK-1R expression in human astroglioma cells (U87 MG) and primary rat astrocytes at both mRNA and protein levels. IL-1β treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 50 publications
9
32
0
Order By: Relevance
“…The increased transcription of PPT-A probably contributed to the increased expression of SP. These observations were in agreement with the results for other models, which also highlighted the involvement of NF-B activation in the increased expression of PPT-A and NK1R (Guo et al, 2004;Reed et al, 2005;Corcoran and Rameshwar, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…The increased transcription of PPT-A probably contributed to the increased expression of SP. These observations were in agreement with the results for other models, which also highlighted the involvement of NF-B activation in the increased expression of PPT-A and NK1R (Guo et al, 2004;Reed et al, 2005;Corcoran and Rameshwar, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…We focused on ATF-2, for two reasons. First, NF-B activation has been well documented in gliomas (33)(34)(35)(36)(37), and second, our prior inhibitor studies indicated that the inhibition of p38 (Fig. 2) significantly diminished the IL-1 induction of TIMP-1 in astrocytes.…”
Section: Timp-1 Expression Is Not Activated By Il-1 In Many Gliomas Bmentioning
confidence: 82%
“…These animals were housed in a temperaturecontrolled room (23)(24)(25) C). They were maintained in individual cages under a light/dark cycle (lights on at 0800, lights off at 2000) and were given free access to food and water.…”
Section: Methodsmentioning
confidence: 99%